Bridging the Antimicrobial Activity of Two Lactoferricin Derivatives in E. coli and Lipid-Only Membranes - Marx, Lisa; Semeraro, Enrico F.; Mandl, Johannes; Kremser, Johannes; Frewein, Moritz P.; Malanovic, Nermina; Lohner, Karl; Pabst, Georg (Frontiers in Medical Technology, 2021)
We coupled the antimicrobial activity of two well-studied lactoferricin derivatives, LF11-215 and LF11-324, in Escherichia coli and different lipid-only mimics of its cytoplasmic membrane using a common thermodynamic framework for peptide partitioning. In particular, we combined an improved analysis of microdilution assays with ζ-potential measurements, which allowed us to discriminate between the maximum number of surface-adsorbed peptides and peptides fully partitioned into the bacteria. At the same time, we measured the partitioning of the peptides into vesicles composed of phosphatidylethanolamine (PE), phosphatidylgylcerol (PG), and cardiolipin (CL) mixtures using tryptophan fluorescence and determined their membrane activity using a dye leakage assay and small-angle X-ray scattering. We found that the vast majority of LF11-215 and LF11-324 readily enter inner bacterial compartments, whereas only 1−5% remain surface bound. We observed comparable membrane binding of both peptides in membrane mimics containing PE and different molar ratios of PG and CL. The peptides' activity caused a concentration-dependent dye leakage in all studied membrane mimics; however, it also led to the formation of large aggregates, part of which contained collapsed multibilayers with sandwiched peptides in the interstitial space between membranes. This effect was least pronounced in pure PG vesicles, requiring also the highest peptide concentration to induce membrane permeabilization. In PE-containing systems, we additionally observed an effective shielding of the fluorescent dyes from leakage even at highest peptide concentrations, suggesting a coupling of the peptide activity to vesicle fusion, being mediated by the intrinsic lipid curvatures of PE and CL. Our results thus show that LF11-215 and LF11-324 effectively target inner bacterial components, while the stored elastic stress makes membranes more vulnerable to peptide translocation.